Transformasi Digital Sistem Pendaftaran Mahasiswa Berbasis Arsitektur Decoupled di Universitas Islam Negeri Raden Fatah Palembang - Muhammad Dhias Habibi; Freddy Kurnia Wijaya; Adib Muhammad Maros (NuCSJo : Nusantara Community Service Journal, 2026)
Digital transformation in higher education requires scalable, responsive, and maintainable information systems. The independent admission system at State Islamic University of Raden Fatah Palembang, which has been running for more than 10 years, faces several issues such as low performance, non-responsive interface, and complex code structure. This study aims to develop a modern admission system using a decoupled architecture with Next.js as the frontend and Laravel as the backend. The method applied is Service Learning, including requirement analysis, system design, implementation, and evaluation. The results indicate improvements in system performance, stability under concurrent access, and efficiency in data management. Furthermore, user experience is enhanced through features such as multi-step forms, auto-save, and interactive dashboards. Therefore, this system supports the university's digital transformation towards a smart campus.